2018
DOI: 10.1002/widm.1243
|View full text |Cite
|
Sign up to set email alerts
|

Learning analytics: A glance of evolution, status, and trends according to a proposed taxonomy

Abstract: Before the emergence of computer‐based educational systems (CBES) whose aims of providing teaching and learning experiences to hundreds even thousands of users, an explosion of information (e.g., students' log data) demands sophisticated methods to gather, analyze, and interpret learners' traces to regulate and enhance education. Thus, learning analytics (LA) arises as a knowledge discovery paradigm that provides valuable findings and facilitates stakeholders to understand the learning process and its implicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 210 publications
(224 reference statements)
1
40
0
Order By: Relevance
“…The fast-developing context of research on LA and MOOCs shows a variety of emerging themes (e.g., Peña-Ayala, 2018;Veletsianos & Shepherdson, 2016) such as MOOC design (Watson et al, 2016), student subpopulations (Kizilcec, Piech, & Schneider, 2013), or student motivation (Koller, Ng, Chuong, & Zhenghao, 2013). However, despite existing research on MOOC design (Watson et al, 2016), it appears that many MOOCs are developed without applying basic instructional design principles (Margaryan, Bianco, & Littlejohn, 2015) as formulated by Reigeluth (2016), for instance.…”
Section: Background and Related Workmentioning
confidence: 99%
“…The fast-developing context of research on LA and MOOCs shows a variety of emerging themes (e.g., Peña-Ayala, 2018;Veletsianos & Shepherdson, 2016) such as MOOC design (Watson et al, 2016), student subpopulations (Kizilcec, Piech, & Schneider, 2013), or student motivation (Koller, Ng, Chuong, & Zhenghao, 2013). However, despite existing research on MOOC design (Watson et al, 2016), it appears that many MOOCs are developed without applying basic instructional design principles (Margaryan, Bianco, & Littlejohn, 2015) as formulated by Reigeluth (2016), for instance.…”
Section: Background and Related Workmentioning
confidence: 99%
“…A substantial volume of literature has been published on using LA as a method to gain insights into learners and their learning [14,30,33]. Although the previous research has significantly contributed to the understanding in the education domain, the studies usually conducted using ad-hoc analyses to answer a specific research question, not gain information that could be used for widespread development and implementation of learning analytics information systems (LAIS).…”
Section: Problem Identification: Design and Development Of Learning Amentioning
confidence: 99%
“…The applications of these technologies in education has coined the term "learning analytics". In previous studies on learning analytics, different practical implications have been identified as related to user behaviour and engagement modeling, predictive analysis, personalization and adaptive learning [7,26,27,30,37].…”
Section: Introductionmentioning
confidence: 99%
“…It provides clues or insights to improve teachers' classes. LA is a knowledge discovery paradigm and as such can help all stakeholders taking part in the learning process to understand its potential and interconnections [3]. Applying LA techniques from data collected in e-learning environments creates opportunities to foster the educational context by providing recommendations to students and teachers.…”
Section: Introductionmentioning
confidence: 99%